2018
DOI: 10.3847/1538-4357/aabdea
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity Variations in the Type II Globular Cluster NGC 6934*

Abstract: The Hubble Space Telescope photometric survey of Galactic globular clusters (GCs) has revealed a peculiar "chromosome map" for NGC 6934. Besides a typical sequence, similar to that observed in Type I GCs, NGC 6934 displays additional stars on the red side, analogous to the anomalous, Type II GCs, as defined in our previous work. We present a chemical abundance analysis of four red giants in this GC. Two stars are located on the chromosome map sequence common to all GCs, and another two on the additional sequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 63 publications
10
53
0
Order By: Relevance
“…ωCen, NGC 6934 Norris & Da Costa 1995;Marino et al 2018), the relatively low star-to-star metallicity dispersion as shown in Fig. 5 is consistent with the conclusions of Carretta et al (2009a), claiming that most of the clusters can be considered mono-metallic regarding the Fe abundance.…”
Section: Metallicitysupporting
confidence: 84%
“…ωCen, NGC 6934 Norris & Da Costa 1995;Marino et al 2018), the relatively low star-to-star metallicity dispersion as shown in Fig. 5 is consistent with the conclusions of Carretta et al (2009a), claiming that most of the clusters can be considered mono-metallic regarding the Fe abundance.…”
Section: Metallicitysupporting
confidence: 84%
“…The first GC where this spread has been observed is ωCen (Norris & Da Costa 1995), a cluster strongly suspected to be the remnant nucleus of a disrupted dwarf galaxy (Freeman 1993;Dinescu et al 1999;Hughes & Wallerstein 2000;Bekki & Freeman 2003;Böker 2008). While the iron spread found in some clusters (M22, Hesser et al 1977;Marino et al 2009Marino et al , 2011Marino et al , 2012Marino et al , 2013Lee 2015) is still controversial (Mucciarelli et al 2015;Lee 2016), the latest works confirm previous finding and the number of clusters where this peculiarity is detected is increasing with time (Marino et al 2018). Recent analysis added M22 (Hesser et al 1977;Marino et al 2009Marino et al , 2011Marino et al , 2012Marino et al , 2013Lee 2015), M2 Lardo et al 2013;Milone et al 2015), M54 (Sarajedini & Layden 1995;Bellazzini et al 2008;Carretta et al 2010a), NGC 1851 Carretta et al 2010c;Yong & Grundahl 2008;Carretta et al 2011), NGC 5286 (Nataf et al 2013;Marino et al 2015), NGC 5824 (Sa-viane et al 2012;Da Costa et al 2014), Terzan 5 (Ferraro et al 2009;Massari et al 2014), M19 (Johnson et al 2015) and NGC 6934 (Marino et al 2018) to the list of clusters with iron spreads.…”
Section: Introductionsupporting
confidence: 61%
“…In this paper we illustrated how massive primordial thick disc GCs can merge or have mass exchanges, a fact that could explain the metallicity spreads observed in a small, but growing (Marino et al 2018), fraction of the massive Galactic GCs. The main results achieved by studying of the long term-evolution of interacting clusters can be summarised as follows:…”
Section: Discussionmentioning
confidence: 97%
“…The sample of all Type II GCs comprises NGC 362, NGC 1261, NGC 1851, NGC 6715 (M 54), NGC 6934, NGC 7078 (M 15), NGC 7089 (M 2) and Terzan 5 (e.g. Marino et al 2009Marino et al , 2015Marino et al , 2018bDa Costa et al 2009;Yong & Grundahl 2008;Yong et al 2014Yong et al , 2016Carretta et al 2010;Johnson et al 2015Johnson et al , 2017Nardiello et al 2018;Ferraro et al 2009;Massari et al 2014).…”
Section: Type II Gcs In the Integral Of Motion Spacementioning
confidence: 99%